Strengths-based positive psychology interventions: a randomized placebo-controlled online trial on long-term effects for a signature strengths- vs. a lesser strengths-intervention - Proyer, René T.; Gander, Fabian; Wellenzohn, Sara; Ruch, Willibald (Frontiers in Psychology, 2015)
Recent years have seen an increasing interest in research in positive psychology interventions. There is broad evidence for their effectiveness in increasing well-being and ameliorating depression. Intentional activities that focus on those character strengths, which are most typical for a person (i.e., signature strengths) and encourage their usage in a new way have been identified as highly effective. The current study aims at comparing an intervention aimed at using signature strengths with one on using individual low scoring (or lesser) strengths in a randomized placebo-controlled trial. A total of 375 adults were randomly assigned to one of the two intervention conditions (i.e., using five signature vs. five lesser strengths in a new way) or a placebo control condition (i.e., early memories). We measured happiness and depressive symptoms at five time points (i.e., pre- and post-test, 1-, 3-, and 6-months follow-ups) and character strengths at pre-test. The main findings are that (1) there were increases in happiness for up to three months and decreased depressive symptoms in the short term in both intervention conditions; (2) participants found working with strengths equally rewarding (enjoyment and benefit) in both conditions; (3) those participants that reported generally higher levels of strengths benefitted more from working on lesser strengths rather than signature strengths and those with comparatively lower levels of strengths tended to benefit more from working on signature strengths; and (4) deviations from an average profile derived from a large sample of German-speakers completing the Values-in-Action Inventory of Strengths (VIA-IS) were associated with greater benefit from the interventions in the signature strengths intervention. We conclude that working on character strengths is effective for increasing happiness and discuss how these interventions could be tailored to the individual for promoting their effectiveness.